Recognition of diverse GATA motifs necessitates multimodal GATA3-DNA binding - Gharui, Sowmomita; Puntambekar, Shraddha; Sarkar, Ram Rup; Narlikar, Leelavati; Sengupta, Durba (Biochemical and Biophysical Research Communications, 2026)
GATA3 is a pioneer transcription factor that plays a central role in the formation, proliferation, and sustenance of various immune cell types, notably serving as the ``master regulator'' of T helper 2 (Th2) cell differentiation. It regulates gene expression by recognizing the canonical DNA consensus motif (A/T)GATA(A/G) through its highly conserved zinc finger domains. However, beyond this classical binding motif, emerging evidence indicates that GATA3 also recognizes a varied array of noncanonical and palindromic sequence motifs, but the underlying molecular mechanisms are unclear. In this review, we discuss an emerging aspect of GATA3 function that links these diverse DNA sequence motifs to varying structural binding modes and finally to differential chromatin outcomes. We discuss how the alternative sequence motifs may engage the two zinc finger domains differently, leading towards a multitude of binding modes underlying this diverse motif recognition. The spacer length between the GATA motifs has been shown to modulate DNA binding and the geometric constraints imposed may help determine the binding mode. We reanalyzed previous data and show that these diverse motifs, as well as the spacers, modulate nucleosomal outcomes, highlighting the importance of these motifs in GATA3 function. Several disease-associated mutations, such as those implicated in autoimmune diseases and cancer, have been reported for GATA3, and we discuss how these mutations alter the binding of the zinc finger domains. This link between sequence recognition and DNA binding modes represents an underexplored aspect of GATA3 function that is necessary for understanding its multifaceted regulatory role in human health and disease.
Keywords: GATA; Mutations; Nucleosome; Palindrome; Reverse palindrome; Spacers; Tandem